An evaluation of the role of technology and relationship in Banking: study on Bangladesh - Huda, S.S.M Sadrul; Chisty, Kazi Khaled Shams; Rashid, Mamunur (BRAC University, 2010)
Banking has become increasingly competitive financial services industry with fragmented customer groups, their heterogeneous expectations and ever-changing global economic challenge. Besides, technology with sophisticated facility is making banking industry new every morning. To be fit against these challenges, it is necessary to appear close to the customers with technology driven long-term stable relationship. Reporting the attitude of the thirty banks' towards technology and relationship, this study documents the imperative importance of technology and relationship in profit maximization, increase in quality of service, reduction in cost of bank operation and diversification of bank income sources. The report shows that Private and Foreign Commercial Banks are pioneers banking facilities with technological development maintaining better relationship with the customers, while local public banks (NCB) are lagging behind.